De-radicalization Efforts Through Religious Moderation for State Islamic University of Raden Fatah Palembang Students - Muhamad Fauzi; Rohmadi Rohmadi (Ta'dib: Jurnal Pendidikan Islam, 2022)
Prejudice and claims of university as center of radicalism seeds appeared, after The National Counterterrorism Agency (BNPT) released that it was successful to create "scared politics" because it was found that there were seven universities which have radical understanding. The purpose of this study was to know Radicalism seeds among of university student and efforts to de-radicalize religious understanding through religious moderation for UIN Raden Fatah Palembang students. This research used qualitative and quantitative methods (mixed methods) through observation, interviews, questionnaires, and documentation technique. The data analysis technique used the Miles and Huberman model for qualitative data and descriptive statistical analysis for quantitative data. The results showed that there were potential seeds for radicalism that occur among 1590 new students (MABA) batch 2021 at UIN Raden Fatah Palembang who had a very low understanding of national commitment, open-minded/ tolerance, anti-violence, and accommodated local culture. The efforts to inculcate religious moderation to de-radicalize religious understanding were: 1) State Islamic University of Raden Fatah Palembang’s Policy in Curriculum Preparation, 2) Religious Student Organizations (Ormawa ) lead to become moderation agents through National Wirakarya Camps, 3) PBAK, Iftitah Lectures, Public Lectures, and Seminar on Strengthening Religious Moderation in Higher Education, 4) Establishing a house of religious Moderation at State Islamic University of Raden Fatah Palembang.